Virtual Social Interaction and Empathy Development in South Korea - Yeji, Seoyeon (Journal of Advanced Psychology, 2025)
Purpose: The purpose of this article was to analyze virtual social interaction and empathy development in South Korea. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Studies in South Korea show that virtual social interactions, especially through immersive VR experiences, enhance empathy development. Programs like Our Neighbor Hero increased prosocial behavior, while high immersion and perspective-taking in VR strengthened empathetic responses. These findings highlight VR’s potential in empathy education. Unique Contribution to Theory, Practice and Policy: Social presence theory, media richness theory & social learning theory may be used to anchor future studies on the virtual social interaction and empathy development in South Korea. Educators, mental health professionals, and organizational leaders are encouraged to adopt multi-modal digital communication strategies that incorporate video conferencing, instant messaging, social media engagement, and online collaborative tools. Funding should be allocated toward research and the development of technologies that not only support mental health initiatives but also foster inclusive, empathetic digital communities